Food Performativity and Transnational Identity in Selected Diasporic Women’s Writings - Sima AGHAZADEH (Cultural Intertexts)
Studying the intersection of food and identity is essential, especially when it interlaces with diasporic cultures. Through the process of immigration and acculturation, food acquires new shapes, meanings and accents, influencing, informing and even transforming our relationship with the world. Incorporating concepts from diasporic discourse such as culinary citizenship, third space and performativity, this paper demonstrates how the use of food narratives and practices in literary works plays a vital performative role in conveying the experiences of individuals living away from home, dealing with displacement and navigating their evolving transnational identities. Food is a cultural zone where different identity determinants intersect and engage in debate. This paper explores how some women writers from different diasporas use food for two primary functions: 1. to negotiate their female characters’ identity in displacement and produce the possibility of replacement, all while navigating the complexities of preserving or reconstructing their cultural identity; and more critically; 2. to enlighten their intended readers about the existing challenges, pains, prejudices and tensions in the assimilation process. In this context, food strategically performs as a discursive and multilayered agent, establishing diversity awareness, challenging exclusionary attitudes and stimulating cross-cultural interactions. Food performativity is both constitutive and reflective of transnational identity construction across political borders—a point not to end here but to begin.